Synthesis of 1-H-3-(2’’-Hydroxy-3’’-substituted-5’’-Chlorophenyl)-5-(2’-Furyl)-2-Pyrazoles and Their Derivatives - Thakare, S.S.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
2-Hydroxy-3-substituted - 5-chlorophenyl - β-(2'-furyl)-acrylophenone dibrrllnide (Ia-c) reacts with hydrazine hydrate in ethanol and yields pyrazole (IIa-c). Similarly, β-(2'-furyl)-acrylophenone dibromide (Ia-c) reacts with phenylhydrazine hydrochloride in ethanol medium and gives 1-phenylpyrazole (IIIa-c). Pyrazole (IIa-c) reacts with acetic acid to form 1-acetyl pyrazole (IVa-c). Also pyrazole (IIa-c) on reaction with benzoylchloride in pyridine gives 1-benzoylpyrazole (Va-c). Characterisation and structural elucidation were done on the basis of chemical reactions, elemental analysis and spectral data.